The Influence of Individual Competence, Organizational Support, and Management Support on Employee Performance at the Malang City DPRD Secretariat Office - Gundisalfus Alwin Par; Syarif Hidayatullah; Stella Alvianna; Roby Nur Akbar (Jurnal Penelitian, 2025)
An important factor supporting the realization of good governance is Human Resources (HR). Quality HR includes the skills, attitudes, knowledge, talents, and performance necessary to carry out tasks and responsibilities within government organizations. The Secretariat of the Regional House of Representatives (DPRD) of Malang City functions as a government agency responsible for the administration of secretarial services. The duties and authorities of the DPRD Secretariat are regulated by Law No. 32 of 2004 and reinforced by Government Regulation No. 41 of 2007 concerning Regional Device Organizations. In carrying out its role, the DPRD Secretariat provides administrative services that support the tasks and functions of the DPRD, including financial administration management. This study aims to analyze the role of individual competence, organizational support, and management support in improving employee performance, as well as to explore the impact of these three factors on the effectiveness, productivity, and work motivation of employees within the organization, with the ultimate goal of identifying the most dominant factor influencing overall employee performance. The research method used is qualitative, utilizing data collection techniques through questionnaires. A questionnaire is a data collection technique that involves forms containing questions to be filled out by several respondents to obtain responses or answers that will be analyzed. The results of this study show that the influence of individual competence, organizational support, and management support significantly and positively affects employee performance. Each of these factors impacts employee performance, with individual competence being the most dominant variable influencing employee performance.